Development of PhET-assisted simulation e-worksheet using flipped laboratory approach for science communication skills - Tri Wahyu Agustina; Epa Paujiah; L. Lestari; Ade Yeti Nuryantini; Yulia Sukmawardani; Riana Lady Flara (University of Muhammadiyah Malang, 2024)
Communication skills are one of the 21st century skills. Specific communication in biology learning includes science communication. The purpose of the study was to analyze the improvement of science communication skills using E-Worksheet assisted by PhET on nervous system material. This research and development consist of three stages: the preliminary study stage, the product development stage and the product testing stage. Static-Group Pretest-Posttest research design. This study involved 35 students in the experimental class and 35 students in the control class selected using Purposive Sampling. The research instrument consisted of a validation questionnaire and limited description with indicators of science communication. Data analysis informs that e-worksheet is very feasible with an average score of 83.83%. The improvement of science communication skills on the nervous system material in the classroom using e-worksheet assisted by PhET simulation with an overall N-Gain value of 0.56 with moderate criteria. E-Worksheet assisted by PhET simulation helps the learning process. The guide to using E-Worksheet assisted by PhET simulation should be clearer and more detailed and provide training for teachers to be more familiar with electronics.